THE RELEVANCE OF ISLAMIC EDUCATION VALUES IN SACRIFICE WORSHIP TO THE LEARNING OF FORMAL EDUCATION - Muhammad Alqadri Burga; Suddin Bani; Usri Usri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This research analyzes the values of Islamic education in the sacrifice worship according to QS al-Ṣaffāt/37: 100-108 and its relevance to the learning of formal education in Indonesia. The type of the research used is qualitative with text study method. Data are collected through documentation and then analyzed using the content analysis method. The results of the research show that the history of sacrifice worship according to QS al-Ṣaffāt/37: 100-108 is divided into four episodes: (1) hope, (2) examination, (3) passing the exam, and (4) reward. There are eight values of Islamic education found in sacrifice worship: (1) faith, (2) morals, (3) patience, (4) resignation, (5) sincerity, (6) democratic, (7) dialogue, and (8) social. The values of Islamic education in the history of kurban worship has relevance to the main characteristics of learning design and the learning process which consists of planning, implementation, evaluation, and follow-up. In addition, it accommodates all values that will be developed in character education.